Ekonomiczne, społeczne oraz prawne aspekty budowy biogazowni rolniczej w regionie łódzkim - Michalak, Dorota (Gospodarka w Praktyce i Teorii, 2011)
Biogas is a renewable energy source which can have a significant contribution to energy production in Poland. The development of renewable energy is a priority task set by the European Union. An important factor affecting the pace of development of the biogas sector is the social aspect. In many cases, the resistance of local communities can lead to the abandonment of the plant. In addition to the financial resources needed to implement the project of the plant, such an investment needs also a series of administrative decisions. Analyzing the economic aspect of the plant are costs, payback period, cost of capital, the possibility of obtaining grants and the location of biogas, namely access to substract and their cost.